Detection of Keratitis in the Cornea by Developing an Active Contour Method Based on Contrast Features - Negoro, Wahyu Saptha; Sumijan, Sumijan; Bukhori, Saiful (Society of Visual Informatics, 2025)
Digital Image Processing (DIP) is a scientific discipline that uses computer image processing techniques. The object of this research is keratitis on the cornea. The image of keratitis is obtained using a slit lamp at Padang Aye Center (PAC) Hospital, based on the results of the diagnosis, namely by looking at the development of the infiltrate or also called hypopyon, measuring the ulcer borders horizontally and vertically to evaluate improvement or response to the treatment given. The clinical results cannot determine the extent and circumference of the keratitis layer area that responds to treatment in the corneal area. The images used were 206 slit lamp images of keratitis. This research provides knowledge in the form of contrast values in the Active Contour method, resulting in an update called Active Contour Contrast Adjustment (ACCA) in correctly segmenting keratitis objects and providing measurements of the area and perimeter of the keratitis area. Overall. The research results from 206 slit lamp images, 195 slit lamp images of keratitis could detect keratitis correctly, and eleven slit lamp images of keratitis could not be detected, resulting in an accuracy of 94.66%. Meanwhile, the standard Active Contour accuracy was not detected at all or 100% undetected. Based on 11 images not detected using the (ACCA) method from 206 images, an accuracy of 5.33% was obtained. So, the results obtained are outstanding and can be used as a reference for medical personnel.